Multimodal postcards to future selves: exploring pre-service language teachers' process of transformative learning during one-year teacher education programme - Maijala Minna (Taylor & Francis, 2022)
Given that teaching is a complex task and that teacher education programmes (TEPs) are usually short, it can be difficult to examine the learning process of pre-service teachers. Based on an analysis of previous studies and empirical research, this study examines the learning process of trainee language teachers during a TEP at a Finnish university. Narrative-like visual and written data were collected from the trainee teachers at the onset (N = 51) and end (N = 43) of the one-year TEP. These multimodal data were qualitatively analysed using transformative learning as the theoretical framework. The results of the study revealed that the trainee teachers encountered several disorienting dilemmas at the start of the programme, mostly related to self-esteem as a teacher, classroom work, and subject-matter knowledge. The change during the TEP was seen especially in the increase of self-confidence and in the motivation to work with learners. Additionally, the findings showed that trainees needed more support from their mentoring teachers, especially in terms of working more creatively in the classroom. Moreover, our study provides a method for how pre-service teachers’ learning processes can be captured and reflected during the TEP.
KEYWORDS:
Pre-service language teachersteacher educationtransformative learning theorydisorienting dilemmamultimodal narratives